Brown Bowel Syndrome Is a Rare and Commonly Missed Disease: A Case Report and Literature Review - Joaquin Ponce-Zepeda; Wenchang Guo; Giorgioni Carmen; Daniel Moon Kim; Gregory C. Albers; Vishal Suresh Chandan; Xiaodong Li (Case Reports in Gastrointestinal Medicine)
Background. Brown bowel syndrome (BBS) is a rare gastrointestinal condition, and vitamin E deficiency has been considered to be a main contributor. However, vitamin E deficiency has been found in only a few patients throughout the published literature studies and its cutoff lab value for diagnosis is not entirely clarified. Case Presentation. A 56-year-old female patient with a history of congenital bowel obstruction (repaired at birth) presented with bloating, abdominal pain, and chronic diarrhea. Endoscopy identified unremarkable gastrointestinal mucosa except a few small polyps in the colon. A partial obstruction was detected by a small bowel follow-through series and then confirmed by CT scan. The resected small bowel was significantly dilated with a thickened brown wall and extensive serosal adhesion. Microscopic examination revealed unremarkable mucosa, but dense granular brown pigments were identified in the cytoplasm of the smooth muscle cells in the muscularis propria. These deposits resulted to be lipofuscin, and BBS was diagnosed. The patient was asymptomatic at 9-month follow-up after surgery without vitamin E supplement. Conclusion. Mitochondrial damage with lipofuscin deposition is at the root of BBS pathogenesis. Any etiology associated with mitochondrial damage can cause this disease, and vitamin E deficiency is just one of them. Dysmotility from extensive serosal adhesion could be a possible etiology for this patient. Due to overlapping symptoms, lipofuscin deposition primarily in the muscularis propria, and unclear serum value of vitamin E, this syndrome is often missed in routine clinical practice from the superficial biopsy. A transmural biopsy is necessary for a definite diagnosis.